Instalação e monitoramento de estação piloto de tratamento de esgoto sanitário visando reúso agrícola - Gomes, Marcus Paulo de Moraes (2014)
The increasing demand for water has made the treatment and reuse of wastewater a topic of global importance. Analyzing scientific and technological advances that deal with this issue, yet, require studies to guide their best job focusing on producing sanitary and environmental effective and economically satisfactory results. Considering this situation, this work aims to install, monitor and evaluate the efficiency of wastewater treatment (ETE) that works through biological processes through measuring the reduction of the organic content of the effluent during the treatment and disposal of agricultural importance of nutrients in the final residue. The ETE has been designed 2500 liters of wastewater per day and is broken down into 4 compartments as follows: septic tank, tank of microalgae with inoculant Desmodesmus subspicatus of anaerobic filter of up flow, wetlands with cultivation of Zantedeschia aethiopica L. Hydraulic detention time is 22 hours and for the checks were allocated 5 points for the collection of samples being the first raw sewage. Monitoring the ETE was developed through the analysis of dissolved oxygen (DO), hydrogen potential (pH), electrical conductivity, turbidity, chemical oxygen demand (COD), biochemical oxygen demand with 5 days incubation at 20° C (BOD520), total nitrogen (NT), total phosphorus (P), potassium (K), calcium (Ca), sodium (Na) and microbiological tests for detection and quantification of total coliforms and E. coli. ETE efficiency reaches approximately 90% of organic matter removal providing an effluent suitable for fertigation, same for Na and Ca elements that have had their levels increased due to the accumulation of organic matter in the anaerobic filter of up flow and wetlands that provide longer detention contain hydraulic gravel in its interior. The ETE acts on nitrogen and phosphorus removal by the action of micro algae and Macrophytes used in the process. It is concluded that, after tertiary treatment for removal of pathogens, this wastewater can be used in Fertigation as NBR 13969/1997, but without discarding periodic monitoring of soil salinity.